Outcomes of the Treatment of Head and Neck Sarcomas in a Tertiary Referral Center - Lindford, Andrew; McIntyre, Benjamin; Marsh, Reginald; MacKinnon, Craig A.; Davis, Charles; Tan, Swee T. (Frontiers in Surgery, 2015)
Head and neck sarcomas are a rare and heterogeneous group of tumors that pose management challenges. We report our experience with these tumors. Forty consecutive patients treated for 44 head and neck sarcomas between 1997 and 2014 were culled from our prospectively maintained head and neck database. Five patients were excluded. The adult cohort consisted 29 (83%) patients of a mean age of 57.7 years, with 33 sarcomas. The most common diagnoses were undifferentiated pleomorphic sarcoma (27%) and chondroblastic osteosarcoma (21%). Clear surgical margins were achieved in 24/33 (73%) lesions. Twenty-two patients received radiotherapy and/or chemotherapy. Fourteen patients developed local (n=6), regional (n=1) and distant (n=7) recurrence. The overall 5-year survival was 66% with a mean survival interval of 66.5 months. Recurrent sarcoma, close (<1mm) or involved surgical margins and advanced age were associated with statistically significantly reduced survival. The pediatric cohort consisted 6 (17%) patients, with a mean age of nine years. Five patients had primary embryonal rhabdomyosarcomas and one had chondroblastic osteosarcoma. Clear surgical margins were achieved in 5 (83%) patients. All patients received adjuvant radiotherapy and/or chemotherapy. Mean survival interval was 102 months. Three patients developed local (n=1) or distant (n=2) recurrence. Twenty-three free and 8 pedicled flaps were performed in 25 patients. 11/39 (28%) lesions in 11 patients developed a complication. In conclusion, head and neck sarcomas are best managed by a multidisciplinary team at a tertiary head and neck referral centre and resection with clear margins is vital for disease control.